Integrating Deep Learning Pedagogy into Sustainable Education Management to Support Agro-Edutourism Development in South Lampung - Sigit Apriyanto; Adelina Anum; Mustaqim Hasan; Fitriya Fitriya; Ahmad Yasir (Journal Corner of Education, Linguistics, and Literature, 2026)
Sustainable education has become a strategic priority in responding to global challenges related to human resource development, environmental sustainability, and local economic empowerment. In agrarian regions such as South Lampung, Indonesia, the integration of education with agro-edutourism offers a contextual learning ecosystem that connects pedagogical processes with real-world practices. This study aimed to systematically examine how Deep Learning pedagogy can be integrated into sustainable education management to support the development of agro-edutourism programs. Employing a Systematic Literature Review (SLR) approach guided by the PRISMA framework, this study synthesizes peer-reviewed articles published between 2019 and 2025 from Scopus, Web of Science, ERIC, and Google Scholar databases. The findings reveal that Deep Learning—characterized by meaningful, reflective, collaborative, and experiential learning—plays a critical role in strengthening adaptive education management, curriculum contextualization, and stakeholder collaboration. The review further highlights the relevance of agro-edutourism as an authentic learning environment that supports sustainability-oriented competencies and community empowerment. This study concludes that integrating Deep Learning pedagogy into sustainable education management provides a strong conceptual foundation for policy and practice in developing agro-edutourism-based education in South Lampung.